Workshop Peningkatan Kompetensi Manajemen dan Administrasi Berbasis TIK bagi Guru dan TU SMKN 8 Merangin - Denmar, Denny; Hendra, Robi; Fitrah, Yundi; Tersta, Friscilla Wulan; Aprillitzavivayarti, Aprillitzavivayarti (Jurnal JUPEMA, 2025)
The Innovation and Efficiency Workshop aims to build the competence of teachers and administrative staff  of SMK in office management and learning administration by optimizing information technology. This activity was carried out at SMKN 8 Merangin as an effort to support the improvement of the quality of education through the use of effective and efficient technology. This workshop includes training on digital office applications, correspondence management systems, and technology-based learning administration management. The learning methods applied are participatory, with group discussions, case studies, and direct practice. The results of the workshop showed an increase in participants' skills in integrating technology into administrative tasks and learning activities. Participants also responded positively by stating that this training was relevant and supported their daily tasks. This workshop is expected to be the basis for sustainable capacity development in the school environment, strengthening administrative governance, and improving the quality of technology-based learning and school management services.  Keywords: innovation, efficiency, teacher competence, office management, learning administration, information technology